Evocação de Ruy Belo na «Terra da Alegria» - Martinho, Fernando J.B. (Revista de Filología Románica, 2009)
Ruy Belo was Lecturer of Portuguese at Universidad Complutense de Madrid from 1971 to 1977. In this article, we study the poems he wrote during that period in which we may find allusions to Madrid (the land of joy to which the title alludes and, at the same time, a synecdoche of Spain), to the streets, squares, restaurants, cafés, theatres, the subway – everything associated with love experiences, portrayed in their contradictions and the effect they have, in moments of exultation or depression, on the perceptions of the surrounding environment by the poet. Allusions to Spanish authors in the poems are also taken into account in the article, especially in two long poems that celebrate Garcilaso, in which we can see how familiar the modern Portuguese poet is with the petrarchist code.